146k views
2 votes
Use the variation of parameters method to solve the DE y"+y'- 2y=1

1 Answer

2 votes

Answer:


y(t)\ =\ C_1.e^(-2t)+C_2e^t-\ t.(e^(-2t))/(3)-(1)/(3)

Explanation:

Given differential equation is,

y"+y'-2y=1


=>\ (D^2+D-2D)y\ =\ 1

To find the complementary function we will write,


D^2+D-2=0


=>\ D\ =\ (-1+√(1^2+4* 2* 1))/(2* 1)\ or\ (-1-√(1^2+4* 2* 1))/(2* 1)


=>\ D\ =\ -2\ or\ 1

Hence, the complementary function can be given by


y(t)\ =\ C_1e^(-2t)\ +\ C_2e^t

Let's say,


y_1(t)\ =\ e^(-2t)\ \ =>y'_1(t)\ =\ -2e^(-2t)


y_2(t)\ =\ e^(t)\ \ =>y'_2(t)\ =\ e^(t)


g(t)\ =\ 1

Wronskian can be given by,


W\ =\ y_1(t).y'_2(t)\ -\ y_2(t).y'_1(t)


=\ e^(-2t).e^(t)\ -\ e^(t).(-2e^(-2t))


=\ e^(-t)\ +\ 2e^(-t)


=\ 3.e^(-t)

Now, the particular integral can be given by


y_p(t)=\ -y_1(t)\int(y_2(t).g(t))/(W)dt\ +\  y_2(t)\int(y_1(t).g(t))/(W)dt


=\ -e^(-2t)\int(e^t.1)/(3.e^(-t))+e^t\int(e^(-2t).1)/(3.e^(-t))dt


=\ -e^(-2t)\int(1)/(3)dt+(e^t)/(3)\int e^(-t)dt


=\ (-e^(-2t))/(3).t\ -\ (e^t)/(3).e^(-t)


=\ -t.(e^(-2t))/(3)-(1)/(3)

Hence, the complete solution can be given by


y(t)\ =\ C_1.e^(-2t)+C_2e^t-\ t.(e^(-2t))/(3)-(1)/(3)

User Avin Varghese
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.